Теоретическая модель сезонных ритмов животных и возможности их проявления у грызунов в условиях Украины - Емельянов, И.Г.; Михалевич, О.А.; Золотухина, С.И. (Вестник зоологии, 1978)
The analysis of the authors’ own data and those from literature resulted in a conclusion that a stable climate favours the formation of animal populations monomorphic according to the phenotype whereas under conditions of an unstable climate the populations are phenotypically polymorphic. It follows that seasonal rhythms in small mammals may be formed only under conditions of a stable climate. In animals whose lifetime exceeds periodicity of seasonal changes in biogeocenoses there are endogenic rhythms, in animals with a short lifelime rhythms of exogenic character are observed.